York Botanical Art Prize - Slatter, Nicole; Slatter, Bruce (2021)
The Impossibility of Demarcation is diptych painting sculpture, responding to the Botanical art Prize theme of contemporary depictions of local flora. The work combines painting and sculptural techniques to consider the impacts of human endeavour on the environment.